“游龙戏凤”故事在不同文学形式中的演变 = An investigation of the transformation and adaptation of the story Youlong Xifeng in different literary forms - 余康宁 Er, Kang Ning (2015)
“游龙戏凤”是流传自明朝正德年间的民间传说，说的大致是明武宗朱厚照微服出巡途中与酒家女李凤的风流韵事。这样的故事难登大雅之堂，因此不被记载入正史内。后人在这个故事基础上进行天马行空的想象，围绕这一个母题创造出不同的文学作品。因为没有正史记载，其凭着传说的口头性和群体性，让人们对这一事件的情节与细节进行虚构，表现出民众对这位明朝皇帝的褒贬态度及评价。本文选取了与“游龙戏凤”传说相关的文学作品，归纳出各文学形式对这一民间传说的演绎，并对故事中的人物刻画进行分析，从中探讨这一则民间传说的传承性和变异性。尽管在不同的文学形式中有不一样的诠释，但仍遵循着同一个母题，在最早的故事基础上加以点缀、删减或混合等，经过了民间传说、戏曲、小说等形式，一直到以影视的呈现方式大有所在。这些传承与创新丰富了“游龙戏凤”这一传说的内容。同时，这些情节各异的文本证明了当时社会与文化因素对民间文学的影响。随后也引来了一些学者的评论，对“游龙戏凤”的商业、文化价值及艺术魅力进行了深入的探索。Youlong Xifeng （游龙戏凤）is a folk legend propagated since Ming Dynasty, which telling about the affairs between Emperor Ming Wuzong and wine-shop lady Li Feng when the emperor toured off the palace. The story is not written down in the history. This has provided the chance of imagination on this story, center around the same motif and create different literature works. Since there is no historical record, people fabricated the plot and the detail of this story, showing their judgement towards this emperor. This thesis will be using literature works related to Youlong Xifeng, generalize the literature significant by examine the plot variations and the portrayal of the characters in order to probe the inheritance and variability of this folk legend. These texts follow the same motif but make enrichment or cancelation on the earliest story and transmitted from the form of drama, novel to film and television work. These inheritance and creativity have enriched the content of this folk legend. At the same time, the variations of the plot have showed the influences of social and culture factors on texts. Some of the works caused reviews from academic, and bring the opportunity to provide the in-depth analysis of the commercial, culture and aesthetic value of the texts.